Does Disappointing European Productivity Growth Reflect a Slowing Trend? Weighing the Evidence and Assessing the Future - John Fernald (International Productivity Monitor, 2020)
In the years since the Great Recession, many observers have highlighted the slow pace of labor and total factor productivity (TFP) growth in advanced economies. This paper focuses on the European experience, where we highlight that trend TFP growth was already low in the runup to the Global Financial Crisis (GFC). This suggests that it is important to consider factors other than just the deep crisis itself or policy changes since the crisis. After the mid-1990s, European economies stopped converging, or even began diverging, from the U.S. level of TFP. That said, in contrast to the United States, there is some macroeconomic evidence for some northern European countries that the GFC had a further adverse impact on TFP growth. Still, the challenges for economic policy look surprisingly similar to the ones discussed prior to the Great Recession, even if the policy implications seem less clear.